Changes on the edge of the downtown. a fragment (2005)
The article is about the formation of city centralities in the Lago – Chicó zone in Bogotá. There is an intrinsic question about the role of urban forms in this process. In some way, the centralities in Bogotá began in residential areas with residential characteristics. The transformation involves a look to the process that controls its conformation, a look to the inherent metabolism of the forms of urban space. Then, the theme is about the control dynamics of physic transformation, that is, morphological changes.